Pengaruh Fundamental Perusahaan, Inflasi, dan Suku Bunga Terhadap Saham Perusahaan Pertanian di BEI : Kata kunci: Saham, Fundamental, Inflasi, Suku Bunga Bank Indonesia - MUHAMMAD ROHMAN TIOVANDI; Sri Widayanti; Prasmita Dian Wijayanti (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
The minimum Knowledge of investor make a lot off loss position on stock market. Purpose of this research is to analyze the influence fundamental factor, inflation and interest rate to the price stock of farm companies on Indonesian stock Exchange.This research use multiple linear regression of ten years financial report of five companies to knowing the influence of fundamental factor,inflation, and interest rate on the stocl price of the companiespartially DER, DAR, and ROA variables have a significant effect on stock prices and simultaneously all factors CR, ROA,DER,DAR, Inflation ,and Interest rate affect 70,5% the company''s stock price and the 29,5% affect by the other factor.DER, DAR, and ROA variables have a significant effect on stock prices and simultaneously all factors affect the company''s stock price